Mengungkap Narasi Sejarah yang Disangkal dalam M/T to Morino Fushigi No Monogatari Karya Oe Kenzaburo - Shobichatul Aminah (Lingua Cultura, 2013)
M/T to Morino Fushigi no Monogatari, a novel by Oe Kenzaburo, offered a different history narration with legitimate history narration of Japan. In Oe’s perspective, the legitimate history of Japan was central to the Emperor. By the novel he attempted to narrate a history from another perspective that was from the perspective of a society of a hidden village in the basin of rural Shikoku forest who were culturally marginalized. The narrator in this novel had a responsibility to continue the narrative tradition to construct village history. The narrator constructed it by taking up history sources from that represent various perspectives. A history constructed by the narrator tended to inverse Japan’s official history, and narrated what is being disclaimed in Japan’s official history. That village history also pointed out that there was not any single version in history narration. Those various history versions coexist and are placed in equality in the novel.